Test–retest reliability of the GAITRite walkway system for the spatio-temporal gait parameters while dual-tasking in post-stroke patients. (24th June 2014) - Cho, Ki Hun; Lee, Hwang Jae; Lee, Wan Hee
Abstract: Purpose : To examine the test–retest reliability of spatio-temporal gait parameters during performance of single- and dual-tasking in post-stroke patients. Method : This study was conducted using a single-group repeated-measures design, involving a baseline measurement session and a follow-up session two days later. Forty-three chronic stroke patients (>6 months) participated in this study. Spatio-temporal gait parameters under the single- and dual-task conditions at a self-selected comfortable gait speed were measured using the GAITRite walkway system. Intraclass correlation coefficients [ICC(2, 1) ] were calculated for determination of reliability between sessions. The level of agreement between the two sessions was determined using Bland–Altman 95% limits of the agreement plots. Results : In all gait parameters, a significant difference was observed between the single- and dual-task conditions ( p < 0.05). For the single condition, ICC (95% CI) was very good for all measures, ranging from 0.98 to 0.99 (0.97–0.99). In addition, for the dual-task condition, ICC (95% CI) was good to very good for all measures, ranging from 0.69 to 0.90 (0.49–0.99). Conclusions : The results of current study demonstrated that the test–retest reliability of the GAITRite system for measurement of spatio-temporal gait parameters under single- and dual-task conditions was good to very good. Therefore, we suggest that measurement of spatio-temporal gait parameters under a dual-task condition using the GAITRite system would be useful for clinical assessment in post-stroke patients. Implications for Rehabilitation: Improvement of walking ability provides opportunities for stroke patients to participate in the community. Our finding, additional cognitive tasks can interfere with the independently basic activities of daily living in stroke patients, may provide basic information for use in development of rehabilitation programs for stroke patients. Spatio-temporal gait parameters under the dual-task condition measured using the GAITRite system may be useful for clinical assessment in post-stroke patients.